2017
DOI: 10.1088/1757-899x/252/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Validation of Various Temperature Modells for Semi-Physical Tyre Model Approaches

Abstract: Abstract. With increasing level of complexity and automation in the area of automotive engineering, the simulation of safety relevant Advanced Driver Assistance Systems (ADAS) leads to increasing accuracy demands in the description of tyre contact forces. In recent years, with improvement in tyre simulation, the needs for coping with tyre temperatures and the resulting changes in tyre characteristics are rising significantly. Therefore, experimental validation of three different temperature model approaches is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…If the speed increases, there will be an increase in tire temperature exceeding 380C, the TKPH value will increase. On the other hand, if the temperature is below 38°C, the TKPH will decrease [24], [25], [26].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…If the speed increases, there will be an increase in tire temperature exceeding 380C, the TKPH value will increase. On the other hand, if the temperature is below 38°C, the TKPH will decrease [24], [25], [26].…”
Section: Resultsmentioning
confidence: 98%
“…And the tire manufacturer concerned issues technical specifications on the TKPH rating value of the tires it produces [23]. Where TKPH is a function of weight (load) and the number of kilometers in 1 hour of operation at a standard temperature of use [6], [24], [25].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the above description, Hc is not expected to be a constant but rather a function of the (rolling) tyre footprint-road contact time; in other words, the Hc coefficient should increase with the tyre rolling speed while decreasing with the footprint length, as hinted at also in ref. [29]. The above observation is the basis of the Hc equation development proposed in Section 3.…”
Section: Heat Transfer Between Road and Tyre-thermophysical Aspectsmentioning
confidence: 85%
“…For example, Miller [24] suggested a value of 3 × 10 4 W/m 2 K. Smith et al [25] proposed one of the most used values, 1.2 × 10 4 W/(m 2 K), employed, as it is, also by [26][27][28], without any discussion about its validity in relation to the testing conditions. Hackl et al [29] found results significantly lower and around 2 × 10 3 W/m 2 K. Taking into account the above discussion, the Hc range seems rather wide, suggesting that its expression should be more complex than a simple constant. To date, there is no evidence that the value 1.2 × 10 4 W/(m 2 K), even if it is the most used, is the correct one, because as far as the authors' knowledge goes, there is not an extensive validation of such a number for all of the possible tyre use conditions.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation